PENGARUH PENUTUPAN DAN SUHU PADA PROSES PEREBUSAN TERHADAP KARAKTERISTIK SIRUP WORTEL (Daucus carota L.) - Widya Puspasari, Desak Putu; Suter, I Ketut; Ayu Nocianitri, Komang (Agrotekno, 2012)
Carrot syrup processing involves thermal boiling process.Unsuitable process will decrease the product quality. Besidestemperature, using uncovered or covered pan also needattention. So how thus effects to the product characteristicneed further study. The aim of this research was to find out:1) effects of covered cooking and temperature oncharacteristic of carrot syrup, and 2) the treatmentscombination yield the best characteristic. This research wasdesigned with factorial randomized block design consist oftwo factors. First factor is cooking method with two level,those are uncovered and covered cooking. Second factor iscooking temperature, consist of four levels, those are 70o,80o, 90o, and 100o C. Each treatment repeated twice so yield16 experiment units.The research showed that interaction between the twotreatments affected the vitamin C content and viscosity.Covered cooking and temperature treatment influenced thebeta-carotene content and the reduction of sugar level. Thetreatments also affected the sensory quality, especially oncolor, flavor, and taste acceptability. Based on the analysis ofall variable, the treatments combination yielding the bestcharacteristic was uncovered cooking treatment ontemperature 70oC. The best treatments characterized by 6,81ppm beta-carotene content; 3,59% reduction sugar level; 4,14mg/100 g vitamin C content; viscosity 81,17 cP; coloredorange type 2 (based on colour-chart), typical of carrotflavor, and acceptable for color, flavor, viscosity, taste, andoverall acceptance.
Keywords: covered cooking, temperature, syrup, carrot